Stability Analysis of a Multigroup SEIR Epidemic Model with General Latency Distributions - Nan Wang; Jingmei Pang; Jinliang Wang (Abstract and Applied Analysis)
The global stability of a multigroup SEIR epidemic model with general latency distribution and general incidence rate is investigated. Under the given assumptions, the basic reproduction number ℜ0 is defined and proved as the role of a threshold; that is, the disease-free equilibrium P0 is globally asymptotically stable if ℜ0≤1, while an endemic equilibrium P* exists uniquely and is globally asymptotically stable if ℜ0>1. For the proofs, we apply the classical method of Lyapunov functionals and a recently developed graph-theoretic approach.